Improvement of corrosion resistance of Zn-Ni alloy coatings by anodizing in selected alcoholic solutions. (September 2019) - Maciej, A.; Wadas, A.; Sowa, M.; Socha, R.; Dercz, G.; Rabe, M.; Simka, W.
Highlights: Anodic treatment has been used to modify the Zn-Ni alloy coatings on steel. Alcoholic solutions were used for the first time for anodizing of Zn-Ni coatings. The obtained passive films were nanometric in thickness which results in colorizing. The coatings had mixed oxide-alkoxide character. Terminal voltage of 20 V was the best for improving the corrosion resistance. Abstract: The subject of this investigation is the anodic treatment of galvanic Zn-Ni alloy coatings in alkaline solutions of selected alcohols and their characterization. The process was carried out galvanostatically at an anodic current density in the range 0.06–6.25 A/dm 2 for 2–60 minutes. The characterization of the formed coatings was based on the morphological studies (OM), determination of the chemical and phase composition (XPS and GIXD), as well as film thickness (UV–vis spectroscopic ellipsometry) and corrosion investigations (EIS). It was found that the coatings have a mixed oxide-alkoxide passive character with the alkoxide-rich layer on the top. The anodic oxidation led to the coloration of the alloy; various colors (beige, blue, and violet) could be obtained depending on the process parameters. The colors were strongly related to the thickness of the films, which is similar to the passive layers found on valve metals (e.g. titanium). The thickest of the conversion coatings had ca. 250 nm. The EIS investigations showed the improvement of corrosion resistance of the substrate after the anodic treatment.